Peran Mediasi Job Satisfaction Dalam Pengaruh QWL Dan Competence terhadap OCB - Nanang Apriliyanto (Journal of Economics and Management (JECMA), 2023)
The purpose of the study was to analyze the effect of quality of work life and competence on job satisfaction of employee in government agencies. To analyze the effect of quality of work life, competence and job satisfaction on Organizational Citizenship Behavior (OCB) employee in the government Kabupaten Kendal. Sampling with census sampling technique which is a sampling technique took all the total population of 82 respondents (researchers not included). The data used are primary data in the form of questionnaires. The data analysis method uses regression analysis. Based on the results of the study note that the quality of work life affects job satisfaction. Competence affects job satisfaction. Quality of work life affects Organizational Citizenship Behavior (OCB). Competence influences Organizational Citizenship Behavior (OCB). Job satisfaction influences Organizational Citizenship Behavior (OCB). Job satisfaction does not mediate the effect of quality of work life on Organizational Citizenship Behavior (OCB). Job satisfaction does not mediate the effect of competence on Organizational Citizenship Behavior (OCB). Keyword: quality of work life, competence, job satisfaction, Organizational Citizenship Behavior.